Acute Kidney Injury After Large Ventral Hernia Repair Requiring Transversus Abdominis Release. Issue 4 (April 2022) - Schaeffer, H. David; Sharp, Nicole E.; Jaap, Kathryn; Semian, John; Alaparthi, Mohanbabu; Sun, Haiyan; Young, Amanda; Factor, Matthew
Background: Acute kidney injury (AKI) is a known postoperative complication of open ventral hernia repair contributing to increased costs, hospital length of stay, and mortality. The aim of this study was to identify whether the muscle injury that occurs in a posterior separation of components via transversus abdominis release (TAR) contributes to a higher incidence of postoperative AKI. Methods: A retrospective cohort study of patients who underwent open retrorectus ventral hernia repair with and without TAR at a single institution between 2012 and 2019 was performed. Patients who underwent a separation of components via either unilateral or bilateral transversus abdominis release were compared to those who did not undergo TAR as part of their hernia repair (non-TAR). The outcome of interest was the development of postoperative AKI. Acute kidney injury was defined as an increase in creatinine of greater than 50% of the preoperative baseline. Univariate and multivariate analyses were performed to determine the influence of TAR on the development of AKI. Results: There were 523 patients who met inclusion criteria, of which 159 (30.4%) had a TAR as part of their retrorectus hernia repair. No differences were found in preoperative characteristics between the TAR and non-TAR group including age, gender, history of kidney disease, or history of diabetes. By contrast, the TAR group had significantly greater median estimated blood loss (100 mL vs 75 mL, P < .01), mean positive intraoperative fluid balance (2255 mL vs 1887 mL, P < .01), and operative duration (321 min vs 269 min, P < .001). The rate of AKI in the TAR group was 11% (n = 18) vs 6% (n = 23, P = .0503) in the non-TAR group. On multivariate analysis controlling for patient characteristics and intraoperative factors, TAR was the only factor with a significantly increased odds of AKI (OR 1.97, 95% CI 0.994-3.905, P = .0521). Conclusions: In patients with large ventral hernias requiring retrorectus repair, performing a TAR is associated with a nearly 2-fold increase in the development of postoperative AKI. These findings suggest that these patients should be optimized perioperatively with emphasis on fluid resuscitation, limiting nephrotoxic medications and monitoring urine output.